The oil flow and artisan fishing in Tramandaí and Imbé – RS: an analysis in the context of environmental justice - Martins Terceiro, Abraão (Ciência e Natura, 2018)
The article deals with artisanal fisheries and oil flow in the cities of Tramandaí and Imbé, in the State of Rio Grande do Sul. Making an analysis in the context of environmental justice, listing a job category and their key players, describing their activities and the main problems faced in front of accident hazards with oil spill and the influence of this sector for the region. The study aims to identify the main recurrent conflicts of the presence of oil activity in the area where such research is justified by the need to reflect on the value of fisheries, considering its great economic importance and for the preservation of the activity of customs and traditionalism in region.